Sustainable and recoverable waste-based magnetic nanocomposites used for the removal of pharmaceuticals from wastewater - Rocha, Luciana S. (2023)
This work aimed at producing easily recoverable magnetic iron-oxide functionalized activated carbons (AC) through environmentally and energetically sustainable methods, evaluating their efficacy towards the removal of the pharmaceuticals diclofenac (DCF) and venlafaxine (VEN) from different aqueous matrices (ultrapure water and wastewater treatment plant effluents). Two AC were prepared by chemical activation of a biomassic industrial waste followed by either conventional (CP) or microwave (MW) pyrolysis. Then, magnetic iron oxide nanoparticles were loaded onto the produced AC. Differences related to the production procedure were not especially remarkable, since both the resulting magnetic composites (MAC-CP and MAC-MW) presented well-developed micropore structures with specific surface areas of 644 and 548 m2 g−1 and saturation magnetization of 32.9 and 22.5 emu g−1, respectively, which conferred them a high adsorptive performance and efficient magnetic recovery from solution. The kinetic data were well described by both pseudo-first and pseudo-second order models. As for the equilibrium data, Langmuir isotherm provided a good fitting, with maximum adsorption capacities ranging between 97 ± 2 and 215 ± 4 µmol g−1 for MAC-CP and between 80 ± 2 and 172 ± 3 µmol g−1 for MAC-MW. Additionally, in binary (DCF and VEN) solutions and wastewater, adsorption onto both MAC was somewhat inhibited due to competitive effects. MW-assisted regeneration of exhausted MAC was effective, as their adsorptive properties and chemical surface features (according to X-Ray photoelectron spectroscopy) remained unchanged. Overall, the produced waste-based magnetic carbon composites simultaneously combine high adsorptive efficiency, easy retrievability and successful regeneration/reutilization.